KESESUAIAN ANTARA CITA-CITA DAN PEMILIHAN PROGRAM STUDI MAHASISWA FAKULTAS AGAMA ISLAM ANGKATAN 2013/1014 - Shobahiya, Mahasri; Lestari, Risma Marno (Universitas Muhammadiyah Surakarta, 2014)
The success of ones learning is influenced by the ideals to be achieved. This study answered about compatibility of dream and selection courses year 2013/2014. By using a quantitative approach this field research leads to the conclusion that, variety of dream year 2013/2014 is to be a teacher IS (36%), lecturers IS (7%), psychologists (2%), enterpreuner (9%) , bank employees (6%), the judge / prosecutor (1%), director (2%), undergraduate (1%), and others (36%). Students of Islamic studies-Tarbiyah that match with mission and objectives of major is quite large (62%), which aspires to be a teacher and lecturer of IS. Students of Islamic law (Sharia) in accordance with the ideals and objectives of faculty mission are very small (3%), which aspires to be a judge year 2013/2014, to be a teacher of IS (36%), lecturers of IS (7%), psychologists (2%), enterpreuner (9 %), bank clerks (6%), the judge / prosecutor (1%), director (2%), undergraduate (1%), and others (36%). Students Prodi PAI-Tarbiyah The dreams that match with its mission and objectives of faculty are quite large ( 62 % ) , who aspires to be a teacher and lecturer of IS. Students of Islamic law ( Sharia) that match with the ideals and objectives of the faculty is very small ( 3 % ) , which aspires to be a judge / prosecutor .